SYSTEMIC LUPUS ERYTHEMATOSUS : CASE REPORT - Ida Ayu Tri Wedari (Universitas Udayana, 2014)
Systemic lupus erythematosus (systemic lupus erythematosus, SLE), an autoimmune disease characterized by the production of antibodies against components of the cellnucleus that is associated with a broad clinical manifestations. Ninety percent of casesof systemic lupus erythematosus attacking a young woman with a peak incidence at 1540yearsofageduringthereproductiveperiodwiththeratioofwomenandmen5:1.Itsetiologyis unclear, allegedly associated with a specific immune response genes in themajor histocompatibility complex class II, HLA-DR2 and HLA DR3. Clinicalmanifestations which appear heterogeneous and involve almost all organ systems of thecondition of the joints and skin of patients with mild to severe disease that attacks thecentral nervous system, lungs, gastrointestinal tract, and kidneys. Treatment is mainlyaimed at controlling the symptoms of the acute attack and suppress symptoms andweight at a level that can be tolerated and prevent organ damage.